Complicity and Redemption: Beyond the Insider/Outsider Research Dichotomy - Pollack, Shoshana (Social justice, 2015)
The article talks about feminist research in criminology and other disciplines, their challenge to white biases and colonial assumptions, and the complexities and multiple axes of power within research methods. Topics include a collaborative study between an academic/practitioner and a formerly incarcerated woman aiming to disrupt conventional methods of research conduct and writing, the subjectivities specific to both parties, and topics like penal spectatorship and women's criminality.